The Effectiveness Of Using Digital Photographs On Teaching Writing Narrative Text For English For Specific Purposes - Fitrana Harintama; Nur Mukminatien; Enny Irawati (Jurnal Pendidikan Humaniora, 2015)
Abstract: The paper reports a study which aims at exploring the effectiveness of digital photographs in helping students to achieve higher writing performance. This research uses quasi experimental de-sign. The participants were two groups of Arabic Literature department of Maulana Malik Ibrahim State Islamic University, Malang which were drawn using random sampling technique. The findings indicate that the posttest result of experimental and control groups are significantly different. The findings suggest that the implementation of digital photographs in the teaching of writing helps the students gain higher scores than the students who are taught using story starters. Key Words: digital photographs, photographs, narrative text, story starters, writingAbstrak: Penelitian ini bertujuan untuk menemukan efektivitas foto digital dalam membantu siswa untuk mencapai kinerja menulis yang lebih tinggi. Penelitian ini menggunakan desain eksperimen ku-asi. Subjek dalam penlitian ini adalah dua kelompok yang berasal dari Prodi Sastra Arab Universitas Islam Negeri Malang Maulana Malik Ibrahim yang diambil menggunakan teknik random sampling. Temuan menunjukkan bahwa hasil posttest dari kelompok eksperimen dan kontrol berbeda secara signifikan. Temuan menunjukkan bahwa pelaksanaan foto digital dalam pengajaran menulis membantu siswa memperoleh skor yang lebih tinggi daripada siswa yang diajar menggunakan cerita permulaan.Kata kunci: foto digital, foto, narasi teks, cerita permulaan, menulis